Visual Outcomes in Pediatric Optic Neuritis - Wan, Michael J.; Adebona, Olumuyiwa; Benson, Leslie A.; Gorman, Mark P.; Heidary, Gena (American journal of ophthalmology, 2014)
To describe the visual outcomes of a large cohort of pediatric patients presenting to a tertiary care pediatric hospital with first-episode optic neuritis. Retrospective, observational cohort study. In a tertiary care pediatric hospital, patients with first-episode optic neuritis and at least 3 months of follow-up over a 10-year period were assessed and followed-up in the ophthalmology department. The main outcome measures were visual acuity at 3 months and 1 year of follow-up, with analysis of risk factors for poor visual outcomes and the time course of visual recovery. Of the 59 pediatric patients with first-episode optic neuritis, 46 had at least 3 months of follow-up and 36 had at least 1 year of follow-up. The mean age was 12.6 years old; 72% were female, 41% had bilateral involvement, 52% had or developed an underlying diagnosis (39% multiple sclerosis, 7% acute disseminated encephalomyelitis, 7% neuromyelitis optica), and 91% received treatment (85% steroids, 7% multimodal). At 1 year, 81% were at least 20/20 and 89% were at least 20/40. A poor visual outcome at 1 year (<20/40) was associated with vision of <20/20 at 3 months (P = 0.041). Other clinical characteristics, including visual acuity at presentation, sex, bilateral involvement, optic nerve edema, and underlying diagnoses were not significantly associated with poor visual outcomes. In this cohort of pediatric patients with optic neuritis, the majority of patients regained normal visual acuity at 1 year, regardless of baseline clinical characteristics.